Designing a Moving Score Game Based on Virtual Reality from a UI/UX Designer Perspective - Fernandes, Roy; Geovanne Farell; Sheanny Ocmi Sakti; Wiki Lofandri (The Future of Education Journal, 2025)
This final project discusses the design process of the Moving Score game based on Virtual Reality (VR), with a focus on developing a User Interface (UI) and User Experience (UX) that are easy to understand for users who are new to virtual reality. The game is designed to train users’ experiences in playing virtual reality through active interaction in an immersive virtual environment. The method used is a prototyping approach that includes observation, prototype development, testing, and revisions based on user feedback. The UI is designed to be simple, intuitive, and responsive to the user's body movements. Evaluation is conducted through SWOT analysis to identify the strengths, weaknesses, opportunities, and challenges of the UI/UX design. The results of the study show that proper implementation of UI/UX in VR games can enhance user engagement and provide an enjoyable and educational gameplay experience.